OUR EXPERIENCE OF ENDOSCOPIC TRANSSPHENOIDAL SURGERY FOR CUSHING’S DISEASE: OUTCOMES AND COMPLICATION RATES IN 48 PATIENTS - Tuğrul Cem Ünal; Metehan Öztürk; İlyas Dolaş; Musa Samet Özata; Duygu Dölen; Ümmü Mutlu; Ayşe Merve Ok; Nurdan Gül; Özlem Soyluk Selçukbiricik; Ayşe Kubat Üzüm; Sema Yarman; Pulat Akın Sabancı; et al. (İstanbul Tıp Fakültesi Dergisi)
Objective: This study aimed to analyze the results of patients who underwent the transsphenoidal endoscopic approach for Cushing’s disease in our department and to determine the surgical outcomes, recurrence and complication rates. Materials and Methods: A single-center retrospective study was performed on 48 patients who underwent endoscopic transsphenoidal surgery for Cushing’s disease in our department between January 2005 and January 2019. Patients who underwent endoscopic transsphenoidal surgery received perioperative supraphysiological glucocorticoid therapy. Patients were evaluated for clinical features and basal cortisol levels without medication use in the last 24 hours when glucocorticoid therapy was reduced to a physiological dose. Patients were also evaluated with steroid replacement durations; the 3rd month, the first year and the last examination blood cortisol levels, 1mg dexametazon suppression test; MRI imaging post-operative in the first 24 hours, the 3rd month and the first year. Results: A total of 48 patients underwent transsphenoidal endoscopic approach. Moreover, 38 patients (79.1%) had biochemical remission 1 year postoperatively. The mean follow-up of duration was 72 months. An additional recurrence of Cushing’s disease was detected in 11 patients (22.9%). Consequently, in our long-term results 27 patients (56.3%) remained in remission. Conclusions: The mortality and morbidity rates of Cushing’s disease are significantly decreased with treatment. Surgery is the first line treatment method for Cushing’s disease. Transsphenoidal endoscopic surgery is a safe and effective treatment method for Cushing’s disease with benefits such as better visualization, providing the opportunity to access parasellar regions, and lower complication rates.